25 Tahun Pembimbing Kemasyarakatan : Sebuah Analisis Bibliometrik - Priyo Subagyo, Panggih; Nisak, Khoirun (Restorative : Journal of Indonesian Probation and Parole System, 2025)
This article utilises bibliometric analysis that aims to summarise several research studies with a common theme, namely probation and parole officers. The source used in this research is Scopus, covering the period from 2000 to 2025. After data reduction was conducted according to the established categories, we obtained 906 documents. The result of the research shows that there is an increasing trend in the number of research studies on probation and parole officers over the years, with 2022 being the peak of the publication number. The most recent research focuses on probation officers and includes keywords such as procedural justice, perception, and social work. Artikel ini menggunakan analisis bibliometrik yang bertujuan untuk merangkum beberapa penelitian dengan tema pembimbing kemasyarakatan. Sumber data penelitian ini diperoleh dari Scopus periode tahun 2000—2025. Setelah dilakukan reduksi data sesuai dengan kategori yang telah ditetapkan, diperoleh 906 dokumen. Hasil penelitian menunjukan bahwa penelitian terkait pembimbing kemasyarakatan mengalami tren peningkatan tiap tahunnya, di mana tahun 2022 menjadi tahun dengan publikasi terbanyak. Fokus terbaru penelitian yang berhubungan dengan pembimbing kemasyarakatan meliputi kata kunci procedural justice, perception, dan social work.